2019
DOI: 10.1055/a-0838-5209
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic Characteristics of the Diabetic Foot With Peripheral Arterial Disease Using the Angiosome Concept

Abstract: Aim To compare temperature changes following a challenge of limb elevation, in 3 forefoot angiosomes between type 2 diabetes mellitus patients with and without peripheral arterial disease (PAD). Methods Participans were categorized in a no PAD, mild PAD or severe PAD group. All underwent thermal imaging, then successive thermal images were taken at 1 min intervals after the lower limbs were elevated for 5 min. Thereafter, the lower limbs were lowered to the original position and imaged after 1 min. Mean temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Both PAD and DPN have been reported to influence foot temperature [23]. In a recent thermal imaging study, participants with PAD had a significantly higher foot temperature than those that did not have PAD [26,27]. In contrast, previous studies have reported a positive correlation between foot temperature and ankle brachial pressure index, implying that people with PAD have a lower foot temperature [28].…”
Section: Monitoring Foot Temperaturementioning
confidence: 95%
“…Both PAD and DPN have been reported to influence foot temperature [23]. In a recent thermal imaging study, participants with PAD had a significantly higher foot temperature than those that did not have PAD [26,27]. In contrast, previous studies have reported a positive correlation between foot temperature and ankle brachial pressure index, implying that people with PAD have a lower foot temperature [28].…”
Section: Monitoring Foot Temperaturementioning
confidence: 95%
“…Infrared thermometers have been utilized in most investigations to measure the foot's temperature at several locations on both sides and compare those locations on opposing feet [21][22][23][24]. According to earlier studies, a temperature differential of more than 2.2°C between identical spots on separate feet for two consecutive days helps predict the development of ulcers [25,26]. A recent study found that the hallux; first, third, and fifth metatarsal heads; the mid-foot, and the heel all had different median temperatures from ambient temperature and that this difference can predict the development of foot ulcers with great sensitivity but poor specificity [27].…”
Section: Monitoring Of Foot Temperaturementioning
confidence: 99%
“…Foot temperature has been correlated to both PAD and DPN [ 23 ]. In recent thermal imaging research, individuals with PAD had considerably higher foot temperatures than those without PAD [ 26 , 27 ]. In contrast, a previous study revealed a positive association between ankle-brachial pressure index and foot temperature, suggesting that persons with PAD have lower foot temperatures [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Due to long-term hyperglycemia, diabetes can cause chronic diseases of various tissues and organs. Among these diseases is peripheral neuropathy caused by diabetes, combined with peripheral vascular disease, which causes excessive mechanical stress leading to the destruction of soft tissue and bone structure of the foot, called diabetic foot [3,4]. Diabetic foot is a serious complication of diabetes, a chronic progressive disease caused by vascular occlusive disease, leading to complications such as ischemia, peripheral neuropathy, and infection [5,6].…”
Section: Introductionmentioning
confidence: 99%